Multiple Lines of Ecological Evidence Support Ancient Contact Between the African Wild Dog and the Dhole - Rocha, Rita Gomes; Gonçalves, João; Tarroso, Pedro; Monterroso, Pedro; Godinho, Raquel (Frontiers in Ecology and Evolution, 2022)
Genomic tools have greatly enhanced our ability to uncover ancient interspecific gene flow, including cases involving allopatric lineages and/or lineages that have gone extinct. Recently, a genomic analysis revealed the unexpected gene flow between the African wild dog and the dhole. The two species have currently highly disjunct and patchy distributions in Africa and Asia, respectively, which are remnants of a much wider past distribution. Yet, no reported evidence of their past contact has ever been documented. By hindcasting the past potential distribution of both species during the Last Glacial Maximum and the Last Interglacial (LIG), validating paleoclimatic reconstructions with fossil evidence, quantifying the intersection of their bioclimatic niches, and assessing interspecific compatibility, we investigate the location and favourable conditions for such contact and its ecological validity. We were able to identify the Levant region in Eastern Mediterranean during the LIG as the most likely for the co-occurrence of the two canids, and to provide evidence of a highly significant overlap of the AWD niche with the dhole wider niche. These results, combined with compatible ecologic traits, provide consistent support for the potential co-occurrence of both canids. We suggest that the ranges of these canids came into contact multiple times during periods resembling LIG, eventually facilitating gene flow in their post-divergence history. Our results are highly supportive of the key role of the Levant in providing connectivity between African and Eurasian faunas and provide further impetus to combine different tools and approaches in advancing the understanding of species evolutionary histories.